Polypharmacy in Infectious Mononucleosis Management: Case Series - Artem A. Ivanov; Tatiana V. Kulichenko (Union of pediatricians of Russia, 2023)
Background. Infectious mononucleosis is acute viral disease that often forces pediatricians, especially in outpatient departments, to prescribe antibiotics. However, viral infections even with prolonged fever and marked intoxication symptoms do not require antibacterial therapy. Unreasonable antibiotics' administration leads to increase in antibiotic resistance, increase of treatment cost, and development of incorrect therapy understanding in patients. Clinical case description. The authors presented 3 clinical cases of infectious mononucleosis with typical course in children. All patients were unreasonably administered antibacterial therapy with three or more drugs in absence of any clinical and laboratory signs of bacterial infection. Conclusion. Patients with infectious mononucleosis do not require antibacterial therapy due to viral origin of the disease, regardless disease course duration and severity, except the cases with confirmed comorbid bacterial infection.